Incorporating Critical Thinking Skills Development Into Maritime English Class - Sari Kusumaningrum (Jurnal Indonesia Sosial Teknologi, 2025)
The term “Critical Thinking” increasingly presents in the world of education and language teaching recently. Critical Thinking skill in English classes is necessary to improve students’ English Competence. In term of Critical Thinking, the students are asked to be more active in the classroom. In the case of passive learners, teacher is the only one who speaks in the front of classroom. Such teachers look upon their students as empty tubes, which require to be filled with information (students centered). This kind of situation will destroy the opportunities for learning and critical thinking. This paper aims at elaborating critical thinking skills development on language learning especially in Maritime English classroom. Considering that Maritime Students are prepared for the world class seafarer, the method of how English are taught is very crucial. And, Critical Thinking support the process of Maritime English learning. The content also involves a presentation of how critical thinking skill is implemented in Maritime English class through some activities in four language skills (Speaking, Listening, Reading, and Writing)